Analisa Perilaku Konsumen dan Nilai Komik Jepang - D Djudiyah (Jurnal Teknik Industri, 2011)
This research was aimed to analysis and described motivations and kinds of consumer values Japanese comics. The methods used in this research is quantitative research. The subject in this research is 35 students State Yunior High School in Malang, which is using incidental sampling techniques. The instrument to collect the data is questionare. The data analysis methods is quantitaive descriptive. The first result of the research are the motivating factor is social needs, egoistic needs, self actualization and safety needs. The second, the values Japanese comics is the picture and the language used in the Japanese comics are more understandable, the topic is varieties and almost the same with Indonesian culture ever it is more realistic storys and the cost is cheaper than American comics.